A Field Study of the Antecedents and Performance Consequences of Perceived Accountability - Mero, Neal P.; Guidice, Rebecca M.; Werner, Steve (Journal of Management, 2014)
Building on theoretical and empirical work considering the implications of accountability on individual behavior, the authors explored the antecedents and consequences of individual perceptions of accountability for job performance. Using data from two field samples, the authors considered whether the manager’s monitoring behavior thought to enhance perceptions of accountability for behaviors and outcomes predicted greater perceived accountability for task performance and interpersonal facilitation performance. They also explored whether perceived accountability mediated the relationship between monitoring behavior and subsequent performance. Hierarchical linear modeling indicated that subordinates of managers whose monitoring behavior reinforced perceptions of accountability perceived greater accountability for performance and that this perception mediated the relationship between managerial monitoring behavior and performance. The implications of these results and directions for future research are discussed.